Proteomic Analysis of Dendritic Filopodia-Rich Fraction Isolated by Telencephalin and Vitronectin Interaction - Furutani, Yutaka; Yoshihara, Yoshihiro (Frontiers in Synaptic Neuroscience, 2018)
Dendritic filopodia are thin, long, and highly mobile protrusions functioning as spine precursors. By contrast with a wealth of knowledge on molecular profiles in spines, little is known about structural and functional proteins present in dendritic filopodia. To reveal the molecular constituents of dendritic filopodia, we developed a new method for biochemical preparation of proteins enriched in dendritic filopodia, by taking advantage of specific and strong binding between a dendritic filopodial membrane protein, telencephalin, and its extracellular matrix ligand, vitronectin. When vitronectin-coated magnetic microbeads were added onto cultured hippocampal neurons, phagocytic cup-like membrane protrusions were formed on dendrites through the binding to telencephalin. Magnetically purified membrane protrusion fraction was subjected to comprehensive mass spectrometric analysis and 319 proteins were identified, many of which were confirmed to be localized to dendritic filopodia. Thus, this study provides a useful resource for studying molecular mechanisms underlying dendritic development, synapse formation, and plasticity.